Praseodymium ion doped perovskite-based reversible proton ceramic battery air electrode material and preparation method thereof

Through the ionic ionic ingot ingotic electrode material, the problem of high cost and environmental impact of cobalt -based materials is solved, the stability of the perovskite structure and the excellent activity of the electrode material, and improved the performance of the reversible proton ceramic battery.

CN119361727AInactive Publication Date: 2025-01-24NANJING TECH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411321576.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The high cost and low performance of existing perovskite air electrode materials limit the industrial application of reversible proton ceramic batteries, especially cobalt-based materials, which are not environmentally friendly.

Method used

BaFeO3-δ-based perovskite electrode material is doped with low-valence, low-electronegativity praseodymium ions (Pr3+/4+) and prepared by the sol-gel method to maintain the stability and activity of the electrode material.

Benefits of technology

The stability of the perovskite structure and the excellent activity of the electrode material are achieved, the cost and environmental impact of the electrode material are reduced, and the performance of the reversible proton ceramic battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361727A_ABST
    Figure CN119361727A_ABST
Patent Text Reader

Abstract

According to the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material and the preparation method, the molecular general formula of the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material is BaFe < 1-x > PrxO < 3-delta >, in the formula, x is greater than or equal to 0.05 and less than or equal to 0.15, and delta is oxygen vacancy content. Comprising the following steps: (a) weighing metal nitrate in a corresponding proportion according to the stoichiometric ratio and the element relationship of the general molecular formula, and dissolving the metal nitrate in water to obtain a mixed solution; adding a complexing agent into the mixed solution, and then adjusting the pH value to 7-8; evaporating water under the condition of heating and stirring; (b) carrying out drying treatment on the praseodymium ion doped perovskite-based reversible proton ceramic battery precursor gelatinous substance; and (c) putting the praseodymium ion doped perovskite-based reversible proton ceramic battery air electrode precursor into a muffle furnace, and performing high-temperature heat treatment in an air atmosphere. The elements in the electrode material are uniformly distributed, and the synthesis method is simple and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic fuel cells and electrolytic cells, and relates to an air electrode material for a ceramic fuel cell, and in particular to a praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material and a preparation method thereof. Background Art

[0002] Hydrogen energy is a representative of zero-carbon non-electric energy. As a clean energy, it has become an important part of future energy transformation.

[0003] Reversible proton ceramic cells (RPCCs) technology can meet the future development needs of hydrogen energy. RPCCs have two modes: batteries and electrolyzers. As fuel cells (PCFCs), they can use a variety of fuels such as hydrogen and ammonia. RPCCs can convert fuel chemical energy into electrical energy with an efficiency of more than 60%, which is much higher than traditional thermal power generation (30% to 50%). As an electrolyzer (PCECs), it can use renewable energy to electrolyze water to produce hydrogen fuel for energy storage, which has a lower energy storage cost than traditional energy storage batteries. Although RPCCs have the above advantages, the high cost and low performance of their air electrode materials currently limit the industrial application of RPCCs. Although commonly used cobalt-based perovskite materials (such as La 0.4 Sr 0.6 Co 0.2 Fe 0.8 O 3-δ and Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ ) has good performance, but the high cost and environmental unfriendliness of cobalt-based perovskite air electrodes limit their commercial use. Therefore, it is urgent to develop new cost-effective, excellent performance, and environmentally friendly electrode materials to promote their industrialization.

[0004] In the periodic table, iron and cobalt are adjacent and have similar reducibility. In addition, Fe is relatively cheap and has relatively little harm to the environment and humans. Therefore, researchers believe that iron-based materials have great potential to replace cobalt-based materials. Among the common iron-based perovskite materials (such as lanthanum ferrite, strontium ferrite and barium ferrite), barium iron perovskite (BaFeO 3-δ ) has better performance; because the ionic radius of Ba is large, the covalency between Fe and O in the perovskite is weaker, so the activity of Fe is stronger. However, the pure perovskite structure is unstable and cannot form a stable cubic perovskite structure. The commonly used method is to dope fixed high-valent cations (such as Zr 4+ , Nb 5+The doped barium iron perovskite B-site material has a stable crystal structure. However, due to the high valence and high electronegativity of the doped cations, the oxygen vacancy concentration and lattice oxygen basicity of the material are reduced, which inhibits the activity and ion transport capacity of the electrode material, thereby causing the performance of the electrode material to deteriorate.

[0005] Therefore, it is necessary to improve the existing perovskite air electrode materials and preparation processes to develop BaFeO with stable structure and excellent performance. 3-δ Perovskite-based electrode materials. Summary of the invention

[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material; the electrode material adopts a low-valent, low-electronegativity metal cation (Pr 3+ / 4+ ) doped BaFeO 3-δ Based on perovskite electrode materials, it can maintain the excellent activity of electrode materials while stabilizing the perovskite structure.

[0007] In order to achieve the above technical objectives, the present invention provides a praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material, whose molecular formula is BaFe 1-x Pr x O 3-δ ,

[0008] Wherein, 0.05≤x≤0.15, δ is the oxygen vacancy content.

[0009] Optimally, x is 0.05, 0.1 or 0.15.

[0010] Further, x is 0.1.

[0011] In order to improve the performance of reversible proton ceramic batteries, another object of the present invention is to provide a method for preparing the above-mentioned praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material, comprising the following steps:

[0012] (a) weighing a corresponding proportion of metal nitrate and dissolving it in water to obtain a mixed solution; adding a complexing agent to the mixed solution and adjusting the pH to 7 to 8; evaporating the water under heating and stirring conditions to obtain a praseodymium ion-doped perovskite-based reversible proton ceramic battery precursor gel-like substance;

[0013] (b) drying the praseodymium ion-doped perovskite-based reversible proton ceramic battery precursor gel material to obtain a praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode precursor;

[0014] (c) placing the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode precursor in a muffle furnace and performing high-temperature heat treatment in an air atmosphere to obtain the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material.

[0015] Optimally, in step (a), the metal nitrate is a mixture of Ba(NO3)2, Fe(NO3)3·9H2O and Pr(NO3)3·6H2O.

[0016] Furthermore, in step (a), the complexing agent is a mixture of ethylenediaminetetraacetic acid and citric acid monohydrate, and the molar ratio of total metal ions in the metal nitrate to ethylenediaminetetraacetic acid and citric acid monohydrate is 1:0.9-1.1:1.8-2.2, preferably 1:1:2.

[0017] Optimally, in step (b), the drying treatment is carried out at a temperature of 160 to 180° C. and for a time of 5 to 10 hours.

[0018] Optimally, in step (c), the high temperature heat treatment is performed by heating the temperature to 900-1100°C at a rate of 3-5°C / min and maintaining the temperature for 5-10 hours.

[0019] Furthermore, in step (c), the high temperature heat treatment is followed by natural cooling to room temperature.

[0020] The present invention adopts metal cation (Pr 3+ / 4+ ) doped barium iron-based perovskite electrode material, the metal cation (Pr 3+ / 4+ ) has a low valence state and low electronegativity, stabilizing the perovskite structure while maintaining the excellent activity and oxygen vacancy concentration of the electrode material, thereby achieving excellent and stable electrochemical activity.

[0021] The present invention prepares the air electrode material of the perovskite-based reversible proton ceramic battery by a sol-gel method, so that the various elements in the electrode material are evenly distributed. The synthesis method is simple and efficient, and high-quality electrode materials can be obtained to improve the performance of the reversible proton ceramic battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The XRD spectra of the oxides after calcination at 1000℃ in air for 10h and then naturally cooling to room temperature: (a) BaFe 1-x Pr x O 3-δ (x=0.05,0.1,0.15) series oxides; (b) BaFe 0.9 Zr 0.1 O 3-δ Oxide.

[0023] Figure 2It is BFP10(BaFe 0.9 Pr 0.1 O 3-δ ) High temperature XRD spectra at different temperature points between 25 and 750 °C.

[0024] Figure 3 BFP10(BaFe 0.9 Pr 0.1 O 3-δ ) XRD spectra before and after treatment in a 3 vol.% H2O atmosphere for 100 hours.

[0025] Figure 4 It is a mixture of BZCYYb electrolyte and BFP10 (BaFe 0.9 Pr 0.1 O 3-δ ) XRD pattern of the air electrode powder after mixing, calcining at 900℃ in air atmosphere and cooling to room temperature.

[0026] Figure 5 It is the BFP05, BFP10, BFP15 series air electrode and the traditional material BFZ10 (BaFe 0.9 Zr 0.1 O 3-δ ) Arrhenius plot of ASR value versus temperature in an atmosphere with a water partial pressure of 5 vol.% H2O.

[0027] Figure 6 It uses Ni+BZCYYb as fuel electrode, BZCYYb as electrolyte, BFP10(BaFe 0.9 Pr 0.1 O 3-δ ) is the SEM image of a single cell with air electrode.

[0028] Figure 7 It uses Ni+BZCYYb as fuel electrode, BZCYYb as electrolyte, BFP10(BaFe 0.9 Pr 0.1 O 3-δ ) are IP and IV curves of the single cell with air electrode at temperatures of 450°C, 500°C, 550°C, 600°C, and 650°C (fuel electrode atmosphere: H2; air electrode atmosphere: dry air).

[0029] Figure 8 It uses Ni+BZCYYb as fuel electrode, BZCYYb as electrolyte, BFP10(BaFe 0.9 Pr 0.1 O 3-δ) is the IV curve of the single cell of the air electrode at temperatures of 450°C, 500°C, 550°C, 600°C, and 650°C (fuel electrode atmosphere: H2; air electrode atmosphere: 20 vol.% H2O-air).

[0030] Fig. 9 The air electrode material BFP10 (BaFe 0.9 Pr 0.1 O 3-δ )Conductivity diagram at 300~800℃.

[0031] Fig.10 It uses BZCYYb as electrolyte and BFP10 (BaFe 0.9 Pr 0.1 O 3-δ ) or BFZ10 as the air electrode in 5 vol.% H2O-air and 40 vol.% H2O-air atmospheres at 550°C. DETAILED DESCRIPTION

[0032] The praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material of the present invention has a molecular formula of BaFe 1-x Pr x O 3-δ , where 0.05≤x≤0.15, δ is the oxygen vacancy content (usually 0≤δ≤1). x is preferably 0.05, 0.1 or 0.15, more preferably 0.1. 3+ / 4+ ) doped barium iron-based perovskite electrode material, the metal cation (Pr 3+ / 4+ ) has a low valence state and low electronegativity, stabilizing the perovskite structure while maintaining the excellent activity and oxygen vacancy concentration of the electrode material, thereby achieving excellent and stable electrochemical activity.

[0033] The preparation method of the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material comprises the following steps: (a) weighing a corresponding proportion of metal nitrate and dissolving it in water to obtain a mixed solution; adding a complexing agent to the mixed solution and adjusting the pH to 7-8; evaporating the water under heating and stirring conditions to obtain a praseodymium ion-doped perovskite-based reversible proton ceramic battery precursor gel-like substance; (b) drying the praseodymium ion-doped perovskite-based reversible proton ceramic battery precursor gel-like substance to obtain a praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode precursor; (c) placing the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode precursor in a muffle furnace and performing high-temperature heat treatment in an air atmosphere to obtain the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material. The various elements in the electrode material are evenly distributed, the synthesis method is simple and efficient, and high-quality electrode materials can be obtained to improve the performance of the reversible proton ceramic battery.

[0034] In step (a), the metal nitrate is a mixture of Ba(NO3)2, Fe(NO3)3·9H2O and Pr(NO3)3·6H2O. The complexing agent is a mixture of ethylenediaminetetraacetic acid and citric acid monohydrate, and the molar ratio of total metal ions in the metal nitrate to ethylenediaminetetraacetic acid and citric acid monohydrate is 1:0.9-1.1:1.8-2.2, preferably 1:1:2. In step (b), the temperature of the drying treatment is 160-180°C and the time is 5-10h. In step (c), the high-temperature heat treatment is heated to 900-1100°C at a rate of 3-5°C / min and kept warm for 5-10h. After the high-temperature heat treatment, it is naturally cooled to room temperature.

[0035] The present invention is further described in detail below in conjunction with specific examples, but the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry.

[0036] Example 1

[0037] This embodiment provides a praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material, whose molecular formula is BaFe 1-x Pr x O 3-δ (abbreviated as BFP), in this embodiment, BaFe 0.9 Pr 0.1 O 3-δ (abbreviated as BFP10);

[0038] The preparation method of the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material is as follows:

[0039] (a) Weigh 13.067 g of Ba(NO3)2, 18.18 g of Fe(NO3)3·9H2O and 2.175 g of Pr(NO3)3·6H2O, and dissolve them in water to obtain a mixed solution; after all the metal nitrates are dissolved, add 29.224 g of ethylenediaminetetraacetic acid (EDTA) and 42.028 g of citric acid monohydrate (CA), and then add an alkaline solution (ammonia water with a mass fraction of 20-30%) to adjust the pH of the mixed solution to 7-8; at the same time, evaporate the water under heating (temperature 90°C) and stirring to obtain a praseodymium ion-doped perovskite-based reversible proton ceramic battery precursor gel-like substance;

[0040] (b) drying the aforementioned precursor gel material (drying temperature is 180° C., time is 10 h) to obtain a praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode precursor;

[0041] (c) The praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode precursor is placed in a muffle furnace, heated to 1000°C at a heating rate of 5°C / min in an air atmosphere, kept warm for 10 hours, and then naturally cooled to room temperature to obtain the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material powder.

[0042] In this embodiment, the dosage of Pr(NO3)3·6H2O is further adjusted so that the molecular formulas of the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode materials are BFP05 (i.e., BaFe 0.95 Pr 0.05 O 3-δ ), BFP15 (i.e. BaFe 0.85 Pr 0.15 O 3-δ ). Figure 1 (a) is the XRD spectrum of a series of powder oxides of BFP05, BFP10 and BFP15 prepared in Example 1 after calcination at 1000°C in air atmosphere for 10 hours and then naturally cooling to room temperature. The results show that BFP05, BFP10 and BFP15 samples all present a cubic perovskite phase.

[0043] Figure 2 The phase structure of BFP10 powder at high temperature is analyzed by high temperature XRD technology in the air from room temperature to 750℃. It can be seen that the position of the main peak of the cubic structure of the main phase of the perovskite in the BFP10 sample shifts to a low angle during the heating process, which is mainly caused by the thermal reduction of Fe ions during the heating process. However, the cubic structure of the main phase of the perovskite remains unchanged, indicating that BFP10 has good thermal stability under high temperature conditions.

[0044] Figure 3 It is the phase structure stability of BFP10 under water vapor conditions. The air electrode in electrolysis mode needs to be exposed to water vapor for a long time. In this embodiment, the phase structure stability of BFP10 under water vapor conditions is tested. The XRD results show that the main peak position of BFP10 is only shifted to a low angle, and no impurity peak is formed. This shows that only the crystal structure expands in high temperature and humid air, and no impurity phase is formed. This result further shows that BFP10 can maintain a stable phase structure under air electrode operating conditions.

[0045] Comparative Example 1

[0046] This example provides a perovskite-based reversible proton ceramic battery air electrode material, whose molecular formula is BaFe 0.9 Zr 0.1 O 3-δ (abbreviated as BFZ10); its preparation method is basically the same as that in Example 1, except that Zr(NO3)3·5H2O is used instead of Pr(NO3)3·6H2O. Figure 1 (b) is the XRD spectrum of the BFZ10 powder oxide prepared in this example after calcination at 1000℃ in air atmosphere for 10h and then naturally cooling to room temperature. Figure 1 b). The results show that the BFPZ10 sample presents a cubic perovskite phase.

[0047] Application Example 1

[0048] This example provides a method for preparing and testing a symmetrical battery using BFP as an electrode. The specific steps are as follows:

[0049] Weigh 1 g of the air electrode powder BFP prepared in Example 1, 10 ml of isopropanol, 2 ml of ethylene glycol, and 0.8 ml of propylene glycol, pour them into a high-energy ball mill, ball mill at 400 r / min for 50 min, and transfer them to the culture bottle with a dropper to obtain the required air electrode slurry.

[0050] The prepared BZCYYb electrolyte was placed on a heating table and preheated at 150°C. The prepared air electrode slurry was evenly sprayed on both sides of the electrolyte using a spray gun under the push of inert gas. After the liquid evaporated completely, the sprayed electrolyte was placed in a high-temperature muffle furnace and calcined at 900°C for 5 hours to obtain the required symmetrical battery, which was used to test the electrochemical impedance of air electrode materials in the temperature range of 450-650°C. The polarization impedance of the BFP10 electrode at 650°C, 600°C, 550°C, 500°C and 450°C in a water partial pressure of 5 vol.% H2O atmosphere was 0.085Ω·cm 2 、0.127Ω·cm 2 、0.166Ω·cm 2、0.369Ω·cm 2 and 1.157Ω·cm 2 ; Its activation energy is 70.9 kJ mol -1 The polarization impedance of the BFP05 electrode at 650℃, 600℃, 550℃, 500℃ and 450℃ in a 5vol.% H2O atmosphere is 0.100Ω·cm 2 、0.155Ω·cm 2 、0.191Ω·cm 2 、0.376Ω·cm 2 and 1.007Ω·cm 2 ; Its activation energy is 62.1 kJ mol -1 The polarization impedance of the BFP15 electrode at 650℃, 600℃, 550℃, 500℃ and 450℃ in a 5vol.% H2O atmosphere is 0.081Ω·cm 2 、0.123Ω·cm 2 、0.209Ω·cm 2 、0.379Ω·cm 2 and 1.151Ω·cm 2 ; Its activation energy is 72.2 kJ mol -1 As Pr in BaFeO 3-δ With the increase of doping content, the electrode impedance does not change much, but the electrode impedance activation energy gradually increases. 3-δ The polarization impedance of (BFZ10)-based perovskite air electrode material at 650℃, 600℃, 550℃, 500℃ and 450℃ in 5 vol.% H2O atmosphere is 0.217Ω·cm 2 、0.396Ω·cm 2 、0.862Ω·cm 2 , 2.359Ω·cm 2 and 8.658Ω·cm 2 ; Its activation energy is 102.4 kJ mol -1 Compared with traditional Zr doping, Pr doping greatly reduces the 3-δ The impedance and activation energy of the air electrode are improved, thereby enhancing the oxygen catalytic activity.

[0051] Figure 4In order to test whether the electrode material will react with the electrolyte, the air electrode BFP10 and the BZCYYb electrolyte were mixed, calcined at 900°C in air atmosphere, and then cooled to room temperature. The XRD results showed that in addition to the diffraction peaks of the BFP10 phase and the electrolyte phase, no other impurity peaks appeared, indicating that the two phases did not react. This result shows that BFP10 and the BZCYYb electrolyte have good chemical compatibility.

[0052] Application Example 2

[0053] This embodiment provides a method for preparing and testing a single cell with BFP10 as the air electrode, and the specific steps are as follows:

[0054] Weigh 1 g of the air electrode powder BFP10 prepared in Example 1, 10 ml of isopropanol, 2 ml of ethylene glycol, and 0.8 ml of propylene glycol, pour them into a high-energy ball mill, ball mill at 400 r / min for 50 min, and transfer them to the culture bottle with a dropper to obtain the required air electrode slurry.

[0055] The prepared Ni-BZCYYb dry-pressed battery sheet was placed on a heating table and preheated at 150°C. The prepared air electrode slurry was evenly sprayed on the electrolyte surface of the dry-pressed sheet using a spray gun under the push of inert gas. After the liquid evaporated completely, the sprayed dry-pressed battery was placed in a high-temperature muffle furnace and calcined at 900°C for 5 hours to obtain the required single cell, which was used to test the battery performance of the air electrode material in the temperature range of 450-650°C. The power density of the BFP10 single cell at 650°C, 600°C, 550°C, 500°C and 450°C was 1306mW·cm -2 、980mW·cm -2 、720mW·cm -2 、505mW·cm -2 and 285 mW·cm -2 .

[0056] 1. Performance analysis of solid oxide symmetric batteries

[0057] In this case, the electrochemical activity of the BFP series air electrodes was first evaluated by electrochemical impedance spectroscopy (EIS). The AC impedance spectrum test temperature range of the BFP|BZCYYb|BFP symmetrical battery is 450-650°C. During the test, a water pump and a vaporizer are used to introduce deionized water into the test device along with air to obtain a "water vapor-air" atmosphere with a water partial pressure of 5 vol.% H2O. The area specific impedance (ASR) value of each temperature point of the air electrode is obtained through electrochemical impedance spectroscopy testing and analysis. The smaller the ASR value, the better the oxygen catalytic activity of the air electrode.

[0058] Figure 5Arrhenius plot showing the ASR value of BFP series (BFP05, BFP10, BFP15) air electrodes in a 5 vol.% H2O atmosphere. The ASR values ​​of BFP05 at 650°C, 600°C, 550°C, 500°C and 450°C are 0.100Ω·cm 2 、0.155Ω·cm 2 、0.191Ω·cm 2 、0.376Ω·cm 2 and 1.007Ω·cm 2 The ASR values ​​of BFP10 at 650℃, 600℃, 550℃, 500℃ and 450℃ are 0.085Ω·cm 2 、0.127Ω·cm 2 、0.166Ω·cm 2 、0.369Ω·cm 2 and 1.157Ω·cm 2 The ASR values ​​of BFP15 at 650℃, 600℃, 550℃, 500℃ and 450℃ are 0.081Ω·cm 2 、0.123Ω·cm 2 、0.209Ω·cm 2 、0.379Ω·cm 2 and 1.151Ω·cm 2 . The three BFP series oxides with different Pr doping ratios all have lower electrode impedance, among which the air electrode with a doping ratio of 10 mol.% has better comprehensive performance in the temperature range of 450-650 ° C after treatment. Therefore, BFP10 with a 10 mol.% Pr doping ratio was finally selected as the object of further study. In order to compare with the traditional high-valent cation Zr(4+) doped BF perovskite material, this example also tested the traditional Zr-doped BF perovskite BaFe 0.9 Zr 0.1 O 3-δ (BFZ10) Electrochemical impedance spectroscopy. The ASR values ​​of BFZ10 at 650℃, 600℃, 550℃, 500℃ and 450℃ are 0.217Ω·cm 2 、0.396Ω·cm 2 、0.862Ω·cm 2 , 2.359Ω·cm 2 and 8.658Ω·cm 2 , which is much larger than the impedance value of the BFP10 electrode. These results confirm that compared with the traditional fixed high-valent cation Zr 4+ Doping, Pr doping is beneficial to increase the oxygen vacancy concentration, thus further promoting the electrochemical activity.

[0059] 2. Scanning Electron Microscope (SEM) Characterization

[0060] Figure 6 This is a SEM image of a single cell with Ni+BZCYYb as the fuel electrode, BZCYYb as the electrolyte, and BFP10 as the air electrode. The SEM test results show that the BFP10 electrode and the BZCYYb electrolyte are still in good contact after the test, which can be attributed to the excellent thermal matching between the BFP10 material and the BZCYYb electrolyte.

[0061] 3. Single battery performance test

[0062] Figure 7 It uses Ni+BZCYYb as fuel electrode, BZCYYb as electrolyte, BFP10(BaFe 0.9 Pr 0.1 O 3-δ ) as the air electrode at temperatures of 450℃, 500℃, 550℃, 600℃, and 650℃. A Ni+BZCYYb-based fuel electrode, BZCYYb-based electrolyte, and BFP10-based air electrode were used to prepare a Ni + The fuel electrode of BZCYYb|BZCYYb|BFP10 supports a single cell. The air electrode atmosphere is dry air, and the fuel electrode uses H2 as fuel. The test results show that the power density of the single cell at temperatures of 650℃, 600℃, 550℃, 500℃ and 450℃ is 1306mW·cm -2 、980mW·cm -2 、720mW·cm -2 、505mW·cm -2 and 285 mW·cm -2 .

[0063] Figure 8 The fuel electrode supported single cell with the structure of Ni+BZCYYb|BZCYYb|BFP10 was used to measure the electrolysis curve of the cell in an atmosphere where the air electrode was 20 vol.% H2O and the fuel electrode was H2. The test results showed that the corresponding current density at 650℃, 600℃, 550℃, 500℃ and 450℃ was -2000mA·cm at a voltage of 1.3V. -2 、-1400mA·cm -2 、-950mA·cm -2 、-580mA·cm -2 and -350mA·cm -2 .

[0064] 4. Conductivity test

[0065] Fig. 9 This is the relationship between the conductivity and temperature of the BFP10 sample in the temperature range of 300-800℃. As can be seen from the figure, as the temperature increases, the electronic conductivity of the material first increases and then decreases, and the electronic conductivity is between 1.32 and 2.8 S·cm -1 The electronic conductivity of the RPCCs electrode material must be greater than 1S·cm -1 requirements.

[0066] 5. Symmetrical battery stability test

[0067] Fig.10 The symmetric cells of structure BFP10|BZCYYb|BFP10 and structure BFZ10|BZCYYb|BFZ10 were tested for 340h stability in 5vol.%H2O and 40vol.%H2O atmospheres, respectively. The impedance growth rate in 5vol.%H2O atmosphere was 5.7×10 -5 Ω·cm 2 ·h -1 , the impedance growth rate in 40 vol.% H2O atmosphere is 1.48×10 -3 Ω·cm 2 ·h -1 For the BFZ10 electrode, the impedance growth rate in 5 vol.% H2O atmosphere is 1.61×10 -3 Ω·cm 2 ·h -1 The impedance growth rate in 40 vol.% H2O atmosphere is 40.43×10 -3 Ω·cm 2 ·h -1 The results show that BFP10 has higher stability, indicating that Pr doping not only improves the performance of the material, but also improves the stability of the material activity.

[0068] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material, characterized in that: Its molecular formula is BaFe 1-x Pr x O 3-δ , Wherein, 0.05≤x≤0.15, δ is the oxygen vacancy content.

2. The praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material according to claim 1, characterized in that: x is 0.05, 0.1 or 0.

15.

3. The praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material according to claim 2, characterized in that: x is 0.

1.

4. The method for preparing the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (a) weighing a corresponding proportion of metal nitrate and dissolving it in water to obtain a mixed solution; Adding a complexing agent to the mixed solution, and adjusting the pH to 7-8; evaporating the water under heating and stirring conditions to obtain a praseodymium ion-doped perovskite-based reversible proton ceramic battery precursor gel-like substance; (b) drying the praseodymium ion-doped perovskite-based reversible proton ceramic battery precursor gel material to obtain a praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode precursor; (c) placing the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode precursor in a muffle furnace and subjecting it to high-temperature heat treatment in an air atmosphere to obtain the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material.

5. The method for preparing the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material according to claim 4, characterized in that: In step (a), the metal nitrate is a mixture of Ba(NO3)2, Fe(NO3)3•9H2O and Pr(NO3)3•6H2O.

6. The method for preparing the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material according to claim 5, characterized in that: In step (a), the complexing agent is a mixture of ethylenediaminetetraacetic acid and citric acid monohydrate, and the molar ratio of total metal ions in the metal nitrate to ethylenediaminetetraacetic acid and citric acid monohydrate is 1:0.9~1.1:1.8~2.2, preferably 1:1:

2.

7. The method for preparing the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material according to claim 4, characterized in that: In step (b), the drying process is carried out at a temperature of 160-180°C and a time of 5-10 hours.

8. The method for preparing the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material according to claim 4, characterized in that: In step (c), the high temperature heat treatment is performed by heating the temperature to 900-1100° C. at a rate of 3-5° C. / min and maintaining the temperature for 5-10 hours.

9. The method for preparing the praseodymium ion-doped perovskite-based reversible proton ceramic battery air electrode material according to claim 8, characterized in that: In step (c), the high temperature heat treatment is followed by natural cooling to room temperature.

Citation Information

Patent Citations

  • Rare-earth element-doped BaFeO3-delta-based ABO3 type perovskite fuel cell cathode material and application thereof

    CN102208662A

  • Proton conductor reversible battery air electrode, preparation method and application

    CN115650312A

  • A-site high-entropy oxygen electrode material, preparation method thereof and reversible proton ceramic electrochemical battery

    CN116525848A

  • Reversible proton conductor type ceramic electrochemical battery cobalt-free air electrode material and preparation and application thereof

    CN116914099A